THU0015 IL2RA Locus is Associated with Joint Damage in a Specific Rheumatoid Arthritis Phenotype. (9th June 2015) - Lόpez-Lasanta, M.; Gonzalez-Alvaro, I.; Maymo, J.; Fernández-Gutierrez, B.; Ureña, I.; Blanco, F.; Cañete, J.; Alperi-Lόpez, M.; Olive, A.; Corominas, H.; Tornero, J.; Erra, A.; et al.
Abstract : Background: Joint damage is a key pathological feature of Rheumatoid Arthritis (RA) and is characterized by a high level of heterogeneity. There is recent evidence suggesting an association of IL2RA and C5orf3 loci with the degree of joint destruction in RA. Objectives: Using a large cohort of RA patients we have performed the validation of this two candidate genes for joint destruction and analyzed in relation to the main disease phenotypes. Methods: A total of 857 RA patients were recruited and their level of joint destruction was measured. The previously reported single nucleotide polymorphisms at IL2RA (rs2104286) and C5orf30 (rs26232) loci were genotyped in the patient cohort using Taqman RealTime-PCR. The two loci were tested for association with the level of joint destruction using linear regression. Clinically relevant variables were analyzed independently with the level of joint damage and in relation to the genetic polymorphisms using linear regression analysis. Results: We found a highly significant association between IL2RA locus SNP rs2104286 with the level of joint destruction in RA ( P =0.0017). In our cohort, variation at C5orf30 locus did not show any evidence of association. Years of disease duration ( P =2.6e-54), number of previous biological therapies ( P =4.3e-9), body-mass index (BMI, P =6.9e-5), Anti-Citrullinated Peptide Antibodies (ACPA) status ( P =0.0001) and Rheumatoid Factor (RF) status ( P =0.009) were also found to be significantly associated with the level of joint damage in RA. The genetic association between IL2RA locus and bone erosions was found to be restricted to autoantibody-positive (74% ACPA-positive, P =0.001; 74% RF-positive, P =0.004) and female (77%, P =0.01) patients. Conclusions: The results of this study confirm the association of IL2RA with joint destruction in RA and suggest that this genetic variation is relevant to a specific patient phenotype. Acknowledgements: This work was supported by the Spanish Ministry of Economy and Competitiveness Strategic Project grants [PSE-010000-2006-6, IPT-010000-2010-36] and the Fondo de Investigaciόn Sanitaria grant [11/0551]. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Disclosure of Interest: None declared